Comparative proteomics of human milk casein fraction collected from women of Korean and Han ethnic groups in China - Wang, Cuina; Lu, Yingcong; Hu, Jia; Yang, Yang; Cheng, Jianjun; Jiang, Shilong; Guo, Mingruo (Frontiers in Nutrition, 2023)
Human breast milk provides neonates with indispensable nutrition and function. Milk protein is one of the main constituents of breast milk. Human milk profiles can be influenced by many factors. The present study aimed to investigate the difference in casein isolated from mature milk of healthy mothers of Korean and Han ethnic groups in China using data-independent acquisition (DIA) proteomics. A total of 535 proteins were identified and quantified in casein fraction samples from both groups. A total of 528 proteins were annotated to 52 Gene Ontology (GO) terms, the majority (94.13%) of which were distributed in the cell and cell parts of the cellular component. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that 106 proteins were involved in 23 pathways, the greatest (36.79%) in carbohydrate metabolism. There were 39 differentially expressed proteins (DEPs)—10 upregulated and 29 downregulated—between Korean and Han milk. The GO function of blood microparticles and KEGG pathway of Staphylococcus aureus infection for DEPs were the most significantly enriched (p < 0.05). Protein-protein interaction analysis revealed a network with 23 DEPs in 47 interactions, and the fibrinogen alpha chain ranked first as the hub protein. These data may provide useful technical guidance for the development of specific infant foods for certain populations.